Pembelajaran matematika melalui pendekatan saintifik untuk meningkatkan kemampuan komunikasi matematis siswa SMK - Kurnia, Gita Afiati; Anriani, Nurul; Hendrayana, Aan (Universitas Sultan Ageng Tirtayasa, 2023)
This research is motivated by the low mathematical communication skills of students based on the results of surveys and previous research. The purpose of this study was to determine and analyze the differences in the improvement of mathematical communication skills and Self Confidence between students who received didactic-based mathematics learning and students who received conventional learning. This research is a quantitative research with quasi-experimental method and pretest – posttest control group design. This research was carried out in class X SMK Negeri 1 Bayah in the 2019/2020 school year by taking samples using random sampling techniques. The instruments used were tests and non-tests, namely mathematical communication tests, while non-tests were observations, interviews, and a Likert Self Confidence scale. Data analysis used the Wilcoxon test because the data were not normally distributed. The results of this study are the improvement of mathematical communication skills and Self Confidence of students who receive didactic-based mathematics learning better than students who receive conventional learning. In addition, students with high initial mathematical abilities are better than students with moderate or low initial mathematical abilities in achieving mathematical communication skills and Self Confidence.